Introducing the Jordan Labor Market Panel Survey 2016 - Caroline Krafft; Rāǧī Asʿad (IZA Journal of Development and Migration, 2021)
This paper introduces the 2016 wave of the Jordan Labor Market Panel Survey (JLMPS). It is an essential reference for users of this innovative and valuable dataset, which adds to the growing series of labor market panel surveys (LMPSs) produced by the Economic Research Forum (ERF). The 2016 wave is a follow-up on the initial 2010 wave. There has been substantial turmoil in the region since 2010, including the onset of the Syrian conflict and the influx of refugees into Jordan. The 2016 wave over-sampled areas with a high proportion of non-Jordanians to be able to represent and examine this important population. The paper describes this sampling strategy, attrition from 2010 to 2016, and weighting that corrects for attrition and accounts for the sampling strategy. We compare key demographic measures and labor market statistics with other sources of data on Jordan to demonstrate the sample's representativeness. The data provide an important opportunity for a detailed analysis of Jordan's changing labor market and society.
Keywords: J00; C81; C83; 330; survey data; public use data; sample weights; labor; refugees; Jordan